PENGGUNAAN EKSTRAK TANAMAN BUAH LANTA (Excoecaria agallocha L.) DALAM PENGENDALIAN HAMA PENGGEREK BATANG (Hexamitodera semivelutina Hell.) PADA TANAMAN CENGKEH (Syzygium aromaticum L.) DI DESA RERER KECAMATAN KOMBI KABUPATEN MINAHASA - Trivandi Efraim Rambi; Jusuf Manueke; Jackson F. Watung; Sandra E. Pakasi (Universitas Sam Ratulangi, 2019)
ABSTRACT Clove (Syzygium aromaticum L.) in English called cloves, is a scented dried flower stalk from the Myrtaceae family. Clove is a native plant of Indonesia, widely used as a main ingredient in Indonesian clove cigarettes. Pests are one of the inhibiting factors in efforts to increase Clove productivity. This study aims to determine the effect of extracts of lanta (Excoecaria agallocha L.) against larvae attack (Hexamitodera semivelutina) on clove plants (Syzygium aromaticum L.) and determine the concentration of lanta fruit extract which is the best in controlling H. semivelutina larvae attacks on clove plants In Rerer Village, Kombi District, Minahasa Regency. The study was conducted in October to December 2019. The study uses a purposive sampling method (Purposive Sampling Method), which is to choose or determine the location and object of research directly. The study consisted of 5 treatments and 4 replications. Each treatment consisted of 5 sample clove trees that had one active H. semivelutina larvae, so the number of sample trees needed was = 100 trees. materials and equipment include lanta fruit, blenders, filters, plastic containers, injection tools, knives / cutters and mobile / camera clay. The results showed that the highest percentage of H. semivelutina larvae hole due to the use of lanta fruit extract was found in treatment D (concentrated extract 20%) that is 100%, then followed by treatment C (concentrated extract 15%) that is 75%, treatment B (concentrated extracts) 10%) is 55% and the lowest is in treatment A (5% concentrated extract), which is 35%. Keywords: E. agallocha, H. semivelutina, Clove